Fractionation mapping software to map ganglionated plexus sites during sinus rhythm. (28th September 2020) - Aksu, Tolga; Yalin, Kivanc; Gopinathannair, Rakesh
Abstract: Ablation of ganglionated plexuses (GPs) is a relatively new technique in patients with vasovagal syncope. Due to individual variation of GP settlement, reproducible GP detection methods are needed to during electrophysiologic study. In the present case, fractionation mapping software of Ensite system was tested to detect localization of GPs and first compared with previously validated fractionated electrograms based strategy.